Growth Governance Nexus: A Case of Pakistan - Nazir, Rabia; ., Mumtaz Anwar (Journal of Economics and Behavioral Studies, 2013)
Good governance has gained tremendous importance in the development agenda of developing economies since 1990s but growth literature gives mixed picture about the role of governance and institutional factors in explaining GDP growth. The present study is an attempt to provide empirical evidence on interlinks between governance and GDP growth. ADF and Johansen co-integration tests are applied for econometric testing of the hypothesis by using time series data from 1984 to 2010. All the variables turned out to be significant with ICRG (proxy used for governance) having positive and significant impact on GDP growth of Pakistan. Results of the study have shown that governance plays major role in determining GDP growth pattern of Pakistan. A complete reform of the political, economic system, judiciary, bureaucracy and a free media are recommended to improve governance and to achieve sustained GDP growth in Pakistan consequently.